2023
DOI: 10.1097/md.0000000000033480
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric features of gastric mucosa in atrophic gastritis: A different pattern between corpus and antrum

Abstract: Atrophic gastritis can cause mucosa thinning, while detailed metrological evidence is lacking. We aimed to compare the morphological features of full-thickness gastric mucosa in antrum and corpus and evaluate the diagnostic performance for atrophy. Gastric cancer patients were prospectively enrolled (N = 401). Full-thickness gastric mucosa was obtained. Foveolar length, glandular length and musculus mucosae thickness were measured. Pathological assessment was conducted using the visual analogue scale of the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As for sites of lesions, AG, and IM were found most frequently at the angle, lesser curvatures of antrum and corpus in order, and less occurred on fundus, greater curvatures of antrum and corpus. [74][75][76][77] Antrum and corpus may be different in mRNA expression, change patterns of morphometric features and function of acid secretion during the precancerous lesions, [78][79][80] which may lead to significant difference in improvement of AG or IM in the antrum versus corpus, but could not explain the nonsignificant difference in the improvement of AG or IM in the antrum versus corpus after H. pylori eradication. In addition, four studies included in this meta-analysis showed that the improvement of AG and IM discriminated in the greater curvature and the lesser curvature, 36,39,43,81 and all the studies included in this meta-analysis supported that improvement of AG and IM after H. pylori eradication in greater curvature was more significant than in lesser curvature.…”
Section: Discussionmentioning
confidence: 99%
“…As for sites of lesions, AG, and IM were found most frequently at the angle, lesser curvatures of antrum and corpus in order, and less occurred on fundus, greater curvatures of antrum and corpus. [74][75][76][77] Antrum and corpus may be different in mRNA expression, change patterns of morphometric features and function of acid secretion during the precancerous lesions, [78][79][80] which may lead to significant difference in improvement of AG or IM in the antrum versus corpus, but could not explain the nonsignificant difference in the improvement of AG or IM in the antrum versus corpus after H. pylori eradication. In addition, four studies included in this meta-analysis showed that the improvement of AG and IM discriminated in the greater curvature and the lesser curvature, 36,39,43,81 and all the studies included in this meta-analysis supported that improvement of AG and IM after H. pylori eradication in greater curvature was more significant than in lesser curvature.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic atrophic gastritis (CAG) is a precancerous gastric lesion or condition in which the gastric mucosa is subjected to long-term bacterial attack and erosion, resulting in a reduction in the intrinsic glands with or without intestinal glandular metaplasia and/or pseudo-pyloric glandular metaplasia[ 1 ]. According to the 2022 Global Cancer Statistics[ 2 ], China ranks first in overall cancer incidence and mortality rates, and third in gastric cancer incidence (39.7/10 million) and mortality (28.9/10 million) rates worldwide[ 3 ], indicating a high public health risk.…”
Section: Introductionmentioning
confidence: 99%